The Influence of a Biopolymer Coating on Selected Surface Properties of Soilless Substrates Made from Coconut Fibre - Maciej Balawejder; Natalia Matłok; Małgorzata Szostek; Maciej Kuboń (Applied Sciences, 2025)
Horticultural substrates based on coconut fibre are among the most commonly used growing media, but with limited durability. This study presents methods for modifying coconut fibre through surface coating with biopolymers, where polymerisation was initiated in the applied solution. Additionally, the suitability of adding pelletised biochar was analysed. A biomonomer derived from wood processing was used both for fibre surface modification and for binding biochar into pellets. Surface modification through biopolymer coating resulted in changes to selected physicochemical properties. It was found that the coating significantly altered the porosity of the substrate. Depending on the type of coconut fibre, the differences in porosity compared to the unmodified substrate ranged from 12 to 24%. This directly influenced bulk density, which is a crucial parameter in the preparation of substrates for plant growth. The surface properties of the modified substrates also affected sorption and retention capacities. From the perspective of plant production, the supply of bioavailable forms of potassium and phosphorus is essential. Coating and the addition of pelletised biochar, regardless of the type of fibre used, significantly increased the release of PO43− and K+ compared to unmodified substrates. The physiological parameters in plants confirmed the suitability of the modified substrates for plant production.